Trademark Identification and Expansion- Using Visual Information Map to Support Trend Analysis - Chen, Rain; Chang, Jo-Han; Chen, Hung-Yuan (Journal of Asian Business Strategy, 2017)
Comprehending global brand identification and expansion is critical because trademarks are one major approach employed by top hundred companies worldwide for staying competitive. This study examined 173 word marks of the top hundred global trademarks, and 60 ordinary consumers participated in this trademark identification experiment. Multidimensional scaling (MDS) was used to assess study participants’ level of similarity of word marks from eight major industries. The present study also built a trademark map to facilitate companies’ trademark-related decision-making. Company managers can use this trademark map approach to assess the identificationy of their trademarks in the industry. Trademark analysis too is useful for exploring trademark expansion, which suppresses the competitors. The results here show that the top hundred global trademarks had a very good identifiability among consumers. In the future, companies can use this analysis method to build their own trademark maps for evaluating the identification and expansion of their trademarks in the industry.